Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1590/s0101-81752004000100006
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da queima da palhada da cana-de-açúcar no ritmo diário de forrageamento de Atta bisphaerica Forel (Hymenoptera, Formicidae)

Abstract: Este trabalho foi conduzido de julho de 2001 a junho de 2002 em uma plantação de cana-de-açúcar em Oratórios, Minas Gerais, Brasil, objetivando investigar o impacto de uma queima controlada de baixa intensidade (235,26 kcal.s-1.m-1) da palhada seca de cana-de-açúcar sobre a atividade forrageadora de A. bisphaerica. Durante todo o período do estudo, uma correlação negativa entre o fluxo de operárias transportadoras de carga vegetal para o ninho com temperatura e com umidade relativa do ar foi observada. Meses c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…The effects of fire on insects and other arthropods can operate through a variety of mechanisms, and at different temporal and spatial scales. For instance, fire can have an immediate effect through direct mortality (Bock & Bock 1990), reducing species abundance (Andersen & Müller 2000;Sanders 2004) or on foraging activity (Araújo et al 2004). Fire is considered an important disturbance on ant communities in areas of fire regime, such as savannas across the world (Andersen & Müller 2000;Hoffmann 2003;Parr et al 2004).…”
Section: 3mentioning
confidence: 99%
“…The effects of fire on insects and other arthropods can operate through a variety of mechanisms, and at different temporal and spatial scales. For instance, fire can have an immediate effect through direct mortality (Bock & Bock 1990), reducing species abundance (Andersen & Müller 2000;Sanders 2004) or on foraging activity (Araújo et al 2004). Fire is considered an important disturbance on ant communities in areas of fire regime, such as savannas across the world (Andersen & Müller 2000;Hoffmann 2003;Parr et al 2004).…”
Section: 3mentioning
confidence: 99%
“…This could sometimes happen in our survey, but most of the times we found that the activity ceased completely during the warmest hours of the day. Garcia (1997) in A. sexdens rubropilosa and Araujo et al (2004) in A. bisphaerica also noted a decline or a cessation of foraging activity in the warmest period of the day during the dry season and, at least for A. sexdens rubropilosa, a concomitant increase in excavation activity. We found a significant correlation between the level of activity of A. capiguara and air temperature.…”
Section: Discussionmentioning
confidence: 95%
“…This species was recorded only once in the pitfall traps in the unburned areas, but nests were often detected in unburned areas. The immediate mortality of colonies of an Acromyrmex species that builds nests on the soil surface occurs in uncontrolled fires in reforested areas (Araújo et al ). The absence of leaf‐cutting ants in the burned areas in our study area may be due to the soil dryness caused by greater sunlight exposure, which can hinder the development of the symbiotic fungus.…”
Section: Discussionmentioning
confidence: 99%